The influence of different alloying elements on the development of the γ/γ′ microstructure of nickel-base superalloys during high-temperature annealing and deformation - Pyczak, Florian; Devrient, Bastian; Neuner, Frank; Mughrabi, Hael (Acta Materialia, 2005)
The development of the γ/γ′ microstructure during high-temperature annealing and deformation is investigated in a series of experimental nickel-base superalloys, with varying contents of alloying elements, in particular rhenium, ruthenium and iridium. Some samples were creep-deformed in compression at 950 °C to different plastic strains εpl, while others were aged at 1000 °C. By investigating the resulting microstructures one can deduce that the development of the γ′ microstructure is influenced in two ways by the alloying elements. The lattice misfit and thereby the coherency stresses between γ′ phase and γ matrix are altered but also the rate of diffusion in the γ matrix. While coherency stresses are the driving force for changes of the γ′ shape at elevated temperatures, the development of the γ′ structure itself is diffusion-controlled. To understand the effects of alloying elements on the development of the γ′ structure, the modifications of both the lattice misfit and the modifications of diffusion rate caused by the alloying elements have to be taken into account. © 2005 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: γ′ Coarsening; γ/γ′ Microstructure; Creep deformation; Microstructural stability; Nickel-base superalloys